2017
DOI: 10.1016/j.amepre.2016.10.036
|View full text |Cite|
|
Sign up to set email alerts
|

Overview of Electronic Nicotine Delivery Systems: A Systematic Review

Abstract: Context Rapid developments in e-cigarettes, or electronic nicotine delivery systems (ENDS), and the evolution of the overall tobacco product marketplace warrant frequent evaluation of the published literature. The purpose of this article is to report updated findings from a comprehensive review of the published scientific literature on ENDS. Evidence acquisition The authors conducted a systematic review of published empirical research literature on ENDS through May 31, 2016, using a detailed search strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
352
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(377 citation statements)
references
References 779 publications
(1,036 reference statements)
17
352
2
6
Order By: Relevance
“…13 Intensive use of e-cigarettes is key to their potential effect as a smoking cessation aid. 14 15 34 Our study, based on the largest representative sample of e-cigarette users in the US in 2014-15, found that more than 70% of recent quitters who used e-cigarettes were still using e-cigarettes daily. The daily use might have been critical in preventing relapse.…”
Section: Comparison With Other Studiesmentioning
confidence: 92%
“…13 Intensive use of e-cigarettes is key to their potential effect as a smoking cessation aid. 14 15 34 Our study, based on the largest representative sample of e-cigarette users in the US in 2014-15, found that more than 70% of recent quitters who used e-cigarettes were still using e-cigarettes daily. The daily use might have been critical in preventing relapse.…”
Section: Comparison With Other Studiesmentioning
confidence: 92%
“…We selected these covariables because other studies have shown that they are significant predictors of e-cigarette use and smoking onset in adolescents. 25,26 The calculation of tolerances and variance inflation factors indicated no problems of multicollinearity among explanatory variables. We report our results as unadjusted and adjusted odds ratios (ORs) with 95% confidence intervals (CIs).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, initial growth in the prevalence of use of these products was noted among cigarette smokers 3. Over time, however, extensive marketing,4 improvements in design, extensive flavor options,5 and a widespread perception that e‐cigarettes were safer than cigarettes led to their increased popularity, especially among youth6, 7, 8, 9, 10 and those who never smoked tobacco 9, 10. This increasing popularity has raised public health concerns, given the paucity of high‐quality longitudinal evidence on the health effects of e‐cigarette exposure and uncertainly about the data supporting their use as smoking‐cessation devices 1…”
Section: Introductionmentioning
confidence: 99%